USING THE SMITH DIAGRAM IN THE ANALYSIS OF HIGH-FREQUENCY ANALOG CIRCUITS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The main objectives of this paper are to learn how to generate impedances on the Smith chart. The Smith diagram is a commonly utilized graphical technique for circuit applications with high frequencies, providing an innovative method for visualizing complex functions in the complex plane, where impedances are represented, as well as in the polar plane, where reflection coefficients (phase and amplitude) are described. Additionally, this allows for the representation of circles with a constant Q (quality factor), continuous standing wave ratio (SWR), and stability circles. Through examples given below, we’ve shown how the admittances and impedances can be graphically analyzed using the Smith chart.
Keywords: Smith diagram; Analog circuits; Reflection coefficient; Voltage standing wave ratio